PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS SOSIAL KOTA KENDARI - Krisna, Krisna; Sarita, Buyung; Saleh, Salma; Hasan, Rachmat Riyaldi; Sumarniwati, Putu (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims to find out (1) The influence of competence and work motivation on employee performance at the Kendari City Social Service. (2) To find out the effect of competence on employee performance at the Kendari City Social Service, (3) To find out the influence of work motivation on employee performance at the Kendari City Social Service. The object in this research is Kendari City Social Service Employees. The population in this study is Kendari City Social Service Employees, totaling 45 employees, the sampling method is saturated sample technique. The data collection method in this study uses a questionnaire (questionnaire). The measurement scale used in this study is the Likert scale. Research data were analyzed using Multiple Linear Regression through SPSS 22 Software. The results of the study show that (1) competence (X1) and work motivation (X2) have a significant effect on employee performance. This shows that by increasing the two variables, namely competence and work motivation, employee performance will increase. (2) Competence has a significant positive effect on employee performance. this shows that with increasing competence, employee performance will increase. (3) Work motivation has a significant positive effect on employee performance. This indicates that with increased work motivation, employee performance will increase.